Kecemasan Orang Tua Berdasarkan Kejadian Speech Delay Pada Balita Di RSUD Ulin Banjarmasin: Speech Delay on Toddlers and Parent’s Anxiety at RSUD Ulin Banjarmasin - Noor Mahmudianti; Malisa Ariani; Nita Hestiyana (Journal of Health, 2023)
Introduction: Develpoment of toddlers is a process where cells on their bodies start to increase. There are a few things that can be evaluated about developments of toddlers, such as, psychomotoric development, social development, speech and language development. If toddlers do not get enough stimulation, a condition called speech delay would occur, so that parents woud experience anxiety. Methods: This stude use descriptive statistical methods. The sample is 69 people with accidental sampling technique. Collecting data using a questionnaire that has beeen testes valid and reliable. Data analysis with tests of mean, median, mode, standard deviation and frequency distribution. Result: Toddlers parents diagnosed with speech delay didn’t experience low anxiety, 13 people experienced moderate anxiety (18.84%), and parents toddlers had speech delay experienced high anxiety a 3 people (4.35%). Toddlers diagnosed with speech delay and other problems parents experienced low anxiety were 1 person (1.45%), parents children had speech delay with other problems experienced moderate anxiety a 45 people (65.22%) and parents children speech delay with other problems experienced high anxiety a 10 people (14.49%). Cognitive aspects of anxiety had highest score with complaints of difficulty sleeping with 6.16%. Conclusion: The anxiety of parents who have speech delay and speech delay toddlers with other problems is the majority of moderate anxiety. Nurses recommended the importance of assessing the anxiety of parents whose children have speech delay from the cognitive aspect